(untitled) - Cogan, Guillaume; Brice, Alexis (Comptes Rendus Biologies, 2025)
Parkinson’s disease (PD) is a multifactorial disorder involving various biological pathways. However, it is more accurate not to define PD as a unique entity, but rather as a mixture of several diseases with similar phenotypes. Attempts to classify subtypes of PD based on the clinical phenotype or biomarkers were tried. Nonetheless, for a subset of individuals, the classification based on the implied gene appears to be the most practical. Although the SNCA gene was the first identified in rare patients, pathogenic variants in GBA1 and LRRK2 are the most common genetic causes or risk factors of PD, and PRKN is the most frequent gene of autosomal recessive PD. Patients with pathogenic variants in SNCA, GBA1, LRRK2 or PRKN show various clinical, anatomopathological and biochemical aspects. Therefore, these four genes associated to PD are of particular interest for the development of targeted therapies. This fact is reinforced by the reality that current approaches are only symptomatic, and no curative treatment is available today. A number of clinical trials aiming to slow or stop disease progression are running, based on the gene involved. In this review, we will discuss the therapeutic approaches targeting SNCA, GBA1, LRRK2 and PRKN.